2009
DOI: 10.1089/aid.2009.0003
|View full text |Cite
|
Sign up to set email alerts
|

In Utero HIV Infection Is Associated with an Increased Risk of Nevirapine Resistance in Ugandan Infants Who Were Exposed to Perinatal Single Dose Nevirapine

Abstract: Use of single dose nevirapine (sdNVP) to prevent HIV mother-to-child transmission is associated with the emergence of NVP resistance in many infants who are HIV infected despite prophylaxis. We combined results from four clinical trials to analyze predictors of NVP resistance in sdNVP-exposed Ugandan infants. Samples were tested with the ViroSeq HIV Genotyping System and a sensitive point mutation assay (LigAmp, for detection of K103N, Y181C, and G190A). NVP resistance was detected at 6–8 weeks in 36 (45.0%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Both genotyping kits were extensively tested and validated (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). While the ViroSeq HIV-1 kit is still on the market, Siemens discontinued selling and supporting the TruGene HIV-1 kit in 2014.…”
mentioning
confidence: 99%
“…Both genotyping kits were extensively tested and validated (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). While the ViroSeq HIV-1 kit is still on the market, Siemens discontinued selling and supporting the TruGene HIV-1 kit in 2014.…”
mentioning
confidence: 99%
“…Importantly, we also found that a substantial proportion (38%) of infants infected in utero who received single-dose nevirapine maintained nevirapine resistance at levels detected by standard population sequencing at 6 months of age compared with 18% of those infected between birth and 14 weeks of age; however, this was not statistically different, but may be limited by the small sample size. Together, these findings highlight differences in the pathogenesis of HIV infection based on timing of infection in children [37][38][39] and emphasize the need to consider timing of infection in the management of HIV-infected children in resource-constrained settings by improving access to HIV testing, including drug resistance testing.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, this study included only infants with in utero HIV infection. Infants who are HIV-infected in utero are more likely to acquire NVP resistance after sdNVP compared to infants who acquire HIV infection at or after birth [3]. …”
Section: Discussionmentioning
confidence: 99%
“…Administration of NVP-based prophylaxis to infants with undiagnosed HIV infection puts those infants at risk for acquiring NVP resistance. When sdNVP is used for prophylaxis, infants with in utero HIV infection are more likely to develop NVP resistance than infants with intrapartum or postnatal HIV infection [3]. In the SWEN study, Ugandan infants with in utero HIV infection who received either sdNVP or sdNVP plus daily NVP up to 6 weeks of age were at high risk of developing NVP resistance [4].…”
Section: Introductionmentioning
confidence: 99%